First report of the South American tomato pinworm Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) and its damage in the Democratic Republic of Congo - Mukwa, Lyna F.T.; Mukendi, J.; Adakate, F.G.; Bugeme, D.M.; Kalonji-Mbuyi, A.; Ghimire, Sita R. (Regional Euro-Asian Biological Invasions Centre Oy (REABIC), 2021)
Tuta absoluta (Meyrick) (Lepidoptera, Gelechiidae), a highly devastating and invasive pest attacking tomatoes either in greenhouses or in open fields, is currently spreading throughout many countries in Africa. Six major vegetable production areas in Kinshasa, Democratic Republic of Congo (DRC), were surveyed between October and November 2016 to report any possible occurrence of the invasive Tuta absoluta. Morphological identification of the sampled adult insect individuals was based on phenotypic characters using a stereomicroscope while molecular identification was carried out using polymerization chain reaction-based approaches targeting the mitochondrial cytochrome oxidase subunit I (COI) gene. Results showed that T. absoluta was found in a commercial tomato farm in Nsele area, while it was absent in the five other sampled sites. Phylogenetic analysis revealed that T. absoluta populations found in Nsele were genetically close to those from Tunisia and Kenya. This is the first report of T. absoluta occurrence and damage in tomatoes grown in DRC where effective and sustainable pest management programs against this invasive insect should be developed and implemented to avoid major crop yield and economic losses.